Pacífico grievance and they/mothers: Esta herida llena de peces by Lorena Salazar Masso (Anclajes, 2023)
Mothers and daughters and sons, the effect of being a mother and the process of becoming one or not being one are widely recognized narratives in literature, film and culture in general. This article traces the Western feminist agendas regarding the experience of motherhood/maternity in order to arrive at the concept of parenthood, to then enter into a dialogue with the novel Esta herida llena de peces (2021) by Colombian writer Lorena Salazar Masso. In it, two mothers who share the same child travel together by river in the midst of a conflict that overwhelms the inhabitants of the Colombian Pacific region, embracing a permanent state of transit and readjustment as the only way to live. Current studies on liminality will serve as the fabric to find those spaces of the novel that link its characters-they/mothers and the Atrato river with the reformulation of social and cultural forces/values. In short, the article tracks those intersections between the experience of parenthood of both mothers and the river as liminal spaces of unceasing transformation.
Keywords: Colombian literature; Lorena Salazar Masso; motherhood; Colombian Pacific; Atrato river